2021
DOI: 10.3389/fimmu.2021.722320
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Receptor CCR5 Links Memory CD4+ T Cell Metabolism to T Cell Antigen Receptor Nanoclustering

Abstract: The inhibition of anabolic pathways, such as aerobic glycolysis, is a metabolic cornerstone of memory T cell differentiation and function. However, the signals that hamper these anabolic pathways are not completely known. Recent evidence pinpoints the chemokine receptor CCR5 as an important player in CD4+ T cell memory responses by regulating T cell antigen receptor (TCR) nanoclustering in an antigen-independent manner. This paper reports that CCR5 specifically restrains aerobic glycolysis in memory-like CD4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…CCL4 may be involved in glucose metabolism through its receptor C-C chemokine receptor 5 (CCR5). It has been reported that the chemokine receptor CCR5 speci cally inhibits aerobic glycolysis in memory-like CD4 + T cells (Blanco et al 2021). CCR5 also regulates insulin signalling in the hypothalamus and contributes to systemic insulin sensitivity and glucose metabolism (Chou et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCL4 may be involved in glucose metabolism through its receptor C-C chemokine receptor 5 (CCR5). It has been reported that the chemokine receptor CCR5 speci cally inhibits aerobic glycolysis in memory-like CD4 + T cells (Blanco et al 2021). CCR5 also regulates insulin signalling in the hypothalamus and contributes to systemic insulin sensitivity and glucose metabolism (Chou et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-β prevents the shift to aerobic glycolysis in in ammatory macrophages and restrains macrophage metabolism (Olson et al 2021). It has also been reported that chemokines, including C-C motif chemokine ligand 4 (CCL4) and CCL5, are to restrain aerobic glycolysis (Blanco et al 2021) and to contribute to systemic insulin sensitivity and glucose metabolism (Chou et al 2016). Therefore, viruses may ultimately have a major impact on host metabolism by modulating the innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…65 Additionally, 2-deoxyglucose (2-DG), which mediates CD8+ T-cell protein synthesis, influences the memory status. 66 The T-cell promoter eIF-2a phosphorylation level and unfolded protein response are significantly reduced in B16-OVA tumour-bearing mice treated with 2-DG for 36 h, which elevates T-cell glycolysis and ATP production and release from mitochondria, contributing to CD8+ T-cell differentiation into Tscms. 67 In conclusion, the aforementioned studies demonstrated the key role of the T-cell metabolic pathway in the circulation-related memory Tcm phenotype, durability and multifunctionality.…”
Section: 12mentioning
confidence: 96%
“…Similarly, impaired amino acid metabolism destabilises the Tm cell amino acid transporter, which on the one hand attenuates mTORC1 signalling, resulting in a slower rate of Tm cell production, and on the other hand, accelerates the acquisition of a effector‐exhaustion phenotype (CXCR3hiCD127lo) in the cells in the peripheral circulation, impeding Teff differentiation into KLRG1‐CD127hi precursor Tm cells (Tpms) and resulting in a decrease in the rate of circulating Tm and a diminished Tm immune response in tumour tissues 65 . Additionally, 2‐deoxyglucose (2‐DG), which mediates CD8+ T‐cell protein synthesis, influences the memory status 66 . The T‐cell promoter eIF‐2a phosphorylation level and unfolded protein response are significantly reduced in B16‐OVA tumour‐bearing mice treated with 2‐DG for 36 h, which elevates T‐cell glycolysis and ATP production and release from mitochondria, contributing to CD8+ T‐cell differentiation into Tscms 67 …”
Section: T‐cell Metabolic Reprogramming and Related Antitumour Immune...mentioning
confidence: 99%
“…Other receptors expressed by T cells, already present in OMIP-069 and involved in stimulating or inhibiting responses, were used to support the full characterization of all described subsets. Those receptors include: CD337, the natural cytotoxicity triggering receptor 3, also known as NKp30, with a role in activating cell cytotoxicity [45]; CCR5 (C-C chemokine receptor type 5) and CCR6 (C-C chemokine receptor type 6), involved in chemokine binding, T cell homing, and memory development [46,47]; CD314, the member D of the activating receptor natural killer group 2, important for NK cell activation [4S]; CD39, the [46] ectonucleoside triphosphate diphosphohydrolase-1 with a role in T regulatory suppressive functions [49], chemokine receptors CXCR3 and CXCR5 which regulate T cell trafficking and priming [50,51] the interleukin-7 receptor a (CD127), involved in memory and effector T cell functions [52]; CD3S, the cyclic ADP ribose hydrolase, important for T cell activation and calcium signaling [53]; and then MHC (Major Histocompatibility Complex) class II receptor, human leukocyte antigen-DR isotype (HLA-DR), widely known for its upregulation during T cell activation [54].…”
Section: Introductionmentioning
confidence: 99%